1994
DOI: 10.1002/ajpa.1330370609
|View full text |Cite
|
Sign up to set email alerts
|

Myth of the typical primate

Abstract: Anthropological interest in nonhuman primates as models for human behavioral evolution has tended to focus on a relatively small number of species. This emphasis, coupled with a search for unifying principles that explain behavior, has led to a widespread perception of the semiterrestrial cercopithecines as "typical," and therefore characteristic of most other primates. The prevalence of male-biased dispersal and female philopatry, the use of aggression to establish and maintain hierarchical relationships, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(92 citation statements)
references
References 208 publications
(344 reference statements)
0
84
0
5
Order By: Relevance
“…Woolly monkeys belong to the ateline subfamily of New World primates, a clade apparently characterized by female dispersal (Rosenberger and Strier, 1989;Strier, 1994). However, although female transfer was confirmed for some populations (Nishimura, 1990;Stevenson et al, 1994), solitary adult and subadult males (as well as an all-male group of five individuals) were also noted at one study site (Di Fiore, unpublished data).…”
Section: Studies Of Dispersal Patternsmentioning
confidence: 98%
“…Woolly monkeys belong to the ateline subfamily of New World primates, a clade apparently characterized by female dispersal (Rosenberger and Strier, 1989;Strier, 1994). However, although female transfer was confirmed for some populations (Nishimura, 1990;Stevenson et al, 1994), solitary adult and subadult males (as well as an all-male group of five individuals) were also noted at one study site (Di Fiore, unpublished data).…”
Section: Studies Of Dispersal Patternsmentioning
confidence: 98%
“…Subsequent studies yet again found discrepancies between data and the model. 6,7 This prompted further updates. In a variant model, Isbell and Van Vuren 8 postulated that the ecological costs of dispersal play a major role in female social relationships.…”
Section: Wranghammentioning
confidence: 99%
“…Some authors previously expressed doubts about the deterministic ends of socioecology. 6,22,28,29 It appears at present that the synthetic model is not repairable. We must give up the dream of a comprehensive model that will encompass all primate societies.…”
Section: 11mentioning
confidence: 99%
“…Females are philopatric and related females reside together in most species, but female dispersal is common in others (Moore 1984;Pusey and Packer 1987a;Strier 1994). Female philopatry is often, but not invariably, related to despotic systems and their variants (Wrangham 1980).…”
Section: Introductionmentioning
confidence: 99%